Effects of Zinc Accumulation on Earthworm Aporrectodea caliginosa (Haplotaxida: Lumbricidae) - Mahmood, Safaa Mohammed; Mohammed, Adnan Musa (Universitas Negeri Surabaya, 2023)
Earthworms are key to the earth's ecosystem, which helps the soil increase its fertility and repair its existing elements, as well as remove contaminants. This study investigated the accumulation of Zn in the earthworm Aporrectodea caliginosa after 15 days of exposure. The worms were grown in media with different concentrations of Zn between 750 and 1500 ppm. Each treatment consisted of three replicates, containing 30 worms. A control group without Zn was also used. Data were analyzed by using Duncan Multi–Range. The results revealed that A. caliginosa had a strong ability to accumulate Zn in its tissue compared to the control group. It was noticed that the increase of the heavy metal in the worm´s tissue is associated with the elevation of the metal in its media. The results show a significant loss of weight in the worm´s body and loss in the growth rate; they also shown a decrease in specific growth rate. Moreover, there was a significant decrease in the worm length, showing a high effect, especially after 15 days of breeding with all concentrations used in this study. The researchers recommend using earthworms to purify the soil from contaminants because earthworm has a great ability to get rid of all pollutants, whether metals or pesticides or parasites, especially in industrialized countries and agricultural lands.